2017
DOI: 10.1038/am.2017.42
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-mediated core/satellite/shell multifunctional nanovehicles for precise imaging of cathepsin B activity and dual-enzyme controlled drug release

Abstract: Intracellular imaging of pathologically relevant proteases can provide essential information for the accurate evaluation of disease stage and progression. However, the risks of degradation by nonspecific enzymes during transportation and poor cellular uptake limit the use of peptide-based molecular probes (PMPs) for in situ protease imaging. To overcome these obstacles, a self-protected nanovehicle with a peptide-mediated core/satellite/shell structure was constructed for precise imaging of the protease cathep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…[172][173][174] For example, benefits of some enzymes like protease and phospholipase, which are responsible for the metastasis and invasiveness of the tumor cells, can be used. [175][176][177][178][179] MMP protein is considered one of the significant changes in the cancerous cell's microenvironment. 180 Many attempts have been made to design a carrier with a responsive reaction to MMPs associated with tumor formation.…”
Section: Mnps@mesoporous Silica Core-shell Drug Carriersmentioning
confidence: 99%
“…[172][173][174] For example, benefits of some enzymes like protease and phospholipase, which are responsible for the metastasis and invasiveness of the tumor cells, can be used. [175][176][177][178][179] MMP protein is considered one of the significant changes in the cancerous cell's microenvironment. 180 Many attempts have been made to design a carrier with a responsive reaction to MMPs associated with tumor formation.…”
Section: Mnps@mesoporous Silica Core-shell Drug Carriersmentioning
confidence: 99%
“…The in vivo experiments have shown that the system can inhibit tumor growth efficiently with minimal side effects. Other studies have investigated on the multifunctional stimulus-responsive nano vehicles that were constructed via peptide mediated core/satellite/shell assembly for targeted protease imaging and controlled drug release [192,193]. Zheng et al used gold nanoclusters based on MSNs through the conjugation of peptide cathepsin B to form MSNs@GNC with a core/satellite structure.…”
Section: Enzyme-responsive Drug Deliverymentioning
confidence: 99%
“…Zheng et al used gold nanoclusters based on MSNs through the conjugation of peptide cathepsin B to form MSNs@GNC with a core/satellite structure. The peptide-mediated core/satellite/shell nanocomplexes could be utilized as multifunctional nanovehicles for precise and dynamic imaging of cathepsin B and of controlled drug release [193].…”
Section: Enzyme-responsive Drug Deliverymentioning
confidence: 99%
“…It has been shown that the monitoring of protease activity was closely related to cancer progression especially in case of Cathepsin B [168]. Among the numerous studies on proteases for such a purpose, hollow mesoporous silica nanoparticles loaded with Dox and conferred with a dual-enzyme sensitivity were conceived for the in situ imaging of Cathepsin B and the release of Dox mediated by proteases ( Figure 19) [169]. An enzymatically dependent FRET process was also used to monitor the payload release from PHPMA prodrug nanocarriers [171].…”
Section: Cathepsins As Probes For Imaging and Theranostic 26mentioning
confidence: 99%
“…(c) Specific delivery, controlled Dox release and intracellular imaging: (i) specific uptake via receptor-mediated endocytosis; (ii) accumulation in endosomes; (iii) endosomal escape and intracellular imaging of Cat B; (iv) Dox release triggered by enzymes. Adapted with permission from Ref [169][170].…”
mentioning
confidence: 99%